2023
DOI: 10.3390/ph16050695
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bifidobacterium breve on the Glycaemic Control, Lipid Profile and Microbiome of Type 2 Diabetic Subjects: A Preliminary Randomized Clinical Trial

Abstract: Type 2 diabetes mellitus (T2DM) is one of the most highly prevalent metabolic disorders worldwide. Uncontrolled T2DM can lead to other health threats such as cardiac arrest, lower-limb amputation, blindness, stroke, impaired kidney function, and microvascular and macrovascular complications. Many studies have demonstrated the association between gut microbiota and diabetes development and probiotic supplementation in improving glycemic properties in T2DM. The study aimed to evaluate the influence of Bifidobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“… 34 56.1 ± 8.2 Placebo 12 weeks 2 Mirjalili [ 72 ] Iran 36 54.5 ± 8.0 B.,L. 36 58.1 ± 9.8 Placebo 12 weeks 2–4 Chaiyasut[ 73 ] Thailand 20 63.9 ± 1.4 B. 20 61.1 ± 1.8 Placebo 12 weeks 2–4 Savytska [ 74 ] Ukraine 34 53.8 ± 9.6 B.L.La.P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 56.1 ± 8.2 Placebo 12 weeks 2 Mirjalili [ 72 ] Iran 36 54.5 ± 8.0 B.,L. 36 58.1 ± 9.8 Placebo 12 weeks 2–4 Chaiyasut[ 73 ] Thailand 20 63.9 ± 1.4 B. 20 61.1 ± 1.8 Placebo 12 weeks 2–4 Savytska [ 74 ] Ukraine 34 53.8 ± 9.6 B.L.La.P.…”
Section: Resultsmentioning
confidence: 99%
“…In the subgroup with intervention duration ≥ 12 weeks, the combination of Bifidobacterium, Lactobacillus, and Lactococcus was the most effective in reducing TG, followed by Bifidobacterium and fish oil. However, it is important to note that in this subgroup, the combination of Bifidobacterium, Lactobacillus and Lactococcus was only used in the study by Sabico [ 58 ], and Bifidobacterium was only reported in the study by Chaiyasut [ 73 ]. Since the two interventions was only used in one study, respectively, our results may be biased due to limited data, and publication bias may exist.…”
Section: Discussionmentioning
confidence: 99%
“…A flow chart of the screening process was shown in Figure 2 . The six included in the literature Kanazawa et al ( 28 ), Chaiyasut et al ( 29 ), Khalili et al ( 30 ), Rustanti et al ( 31 ), Toejing et al ( 32 ), Firouzi et al ( 33 ) were all RCT trials, and their interventions included gut probiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the present study found significant correlations between the relative abundances of genus Bifidobacterium and species Bifidobacterium_longum and the serum TG and HCY levels. This suggested that these microbes might be associated with lipid and homocysteine metabolisms in the early stage of LVO stroke 24 , 27 29 . Meanwhile, in our analyses, the serum TG levels of LVO patients could mediate the effects of species Bifidobacterium_longum on the ischemic stroke severity and functional outcome at discharge, which also provided a new insight on high TG as the risk factor of stroke 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%